Tindak Tutur Direktif Pada Kumpulan Cerpen Rokat Tase Karya Muna Masyari - Ratnasari Ratnasari; Eva Ardiana Indrariani; H.R. Utami (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
The aim of this research is to describe and analyze the form of directive speech acts and the background of the speech in the short story collection Rokat Tase by Muna Masyari. This research is a type of qualitative research. The approach used is a sociopragmatic approach. The data collection techniques used are listening techniques and note-taking techniques. The instrument used is a data card for the classification of forms of directive speech acts. The analysis technique used is descriptive analysis technique. Presentation of the results of data analysis is carried out informally. The forms of directive speech acts found were (9) directive speech acts of giving advice, (31) directive speech acts of commands, (8) directive speech acts of requests, (3) directive speech acts of ordering, and () directive speech acts of criticism. Meanwhile, the background causes of speech are influenced by physical environmental factors, social influences, culture, social status, social relationships and work. This research can have implications for literature learning at junior high school level.